Prototype Hermetic Teachings: Hermes Trismegistus and Three Hermes - V. V. Vinokurov (Концепт: философия, религия, культура, 2021)
The paper treats the topic of hermeticism — an esoteric tradition of teachings — with the view to its origins and varying interpretations. In setting research objectives, the text aims at identifying the common structural foundations of myths and ideas of the hermetic genesis and to establish the main vectors of the formation and transformation of esoteric teachings presented in the spiritual domain and reflected in the material culture of Western Europe from the 4th century BC to the present. For the needs of such a comparative study that embraces philosophical, religious and historical phenomena of culture, the following methods are used. As it is mostly the texts that are analyzed, the methodological framework consists of the interpretation of texts and artifacts – all along the line of presentation of historical sequences, of their recursion, of structural and functional aspects. The sources included not only texts, mathematical operations and chemical formulas of previously known alchemic artifacts are also introduced into the comprehensive analysis. The examination of cultural phenomena leads to the systematization of religious origins, historical and philosophical traditions and scientific achievements that underlie the formation of hermeticism. This structuralisation is possible due to the tools for the analysis of the hermetic body developed in this text. The mapping of the historical development of hermeticism is proposed in a three-level paradigm model based on the image of the Thrice-Great Hermes. It is concluded that the basis of the image of Hermes is the invariant of the historical three-level model of cognition of esoteric teachings, for descriptions of which the terms of ABC — paradigm are introduced. Each of the Hermea has own disciplinary paradigm. The first level of Hermes I, the author of cosmogonic visions, A — paradigm, is represented by inner visions (revelations of the cosmic mind or daimonic visions), thus forming the cultural level of mythology, theology. The level of Hermes II, the founder of writing and counting, lies in the realm of concepts of visions ‒ e.g. the Platonic philosophy, geometry, mathematics (B — paradigm). The third level (C — paradigm) is represented by texts and alchemical artifacts (Alexandrian crystal) of Hermes III, the founder of the art of healing and chemistry, that further embodied in empirical sciences, chemistry and astronomy, as well as ancient technological knowledge of the production of metals, glass and dyes. In general, all hermetic disciplines and practices emerge on the basis of this three-level paradigm.